2009
DOI: 10.3109/00498250903330348
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the porcine constitutive androstane receptor (CAR) and its splice variants

Abstract: Porcine constitutive androstane receptor (CAR; NR1I3) was cloned and compared for homology and activity with mouse and human CAR (mCAR, hCAR). Porcine CAR (pgCAR) was 86% and 75% homologous to hCAR at the nucleotide and protein levels. Five alternatively spliced variants of pgCAR were identified, each of which generated a truncated protein product. Real-time polymerase chain reaction (PCR) analyses showed that these variants were present in pig liver cDNA samples from 4.61% to 9.20% of total pgCAR. pgCAR and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Functional analysis of four SNPs, localized in the ligand binding domain of CAR, (His246Arg, Leu308Pro, Asn323Ser, and Val133Gly) revealed that His246Arg is associated with decreased CAR activation by CITCO, while Leu308Pro affect basal but not chemically stimulated CAR activation in cell-based reporter assays 131; 132 . Recently, a number of naturally occurring alternative splicing variants of human CAR have been identified 133; 134; 135 . Functional characterization of these spliced CAR transcripts revealed that some are associated with altered expression, cellular localization, and chemical response of the receptor 136; 137; 138; 139 .…”
Section: Xenobiotic Receptor and Oxazaphosphorine Metabolismmentioning
confidence: 99%
“…Functional analysis of four SNPs, localized in the ligand binding domain of CAR, (His246Arg, Leu308Pro, Asn323Ser, and Val133Gly) revealed that His246Arg is associated with decreased CAR activation by CITCO, while Leu308Pro affect basal but not chemically stimulated CAR activation in cell-based reporter assays 131; 132 . Recently, a number of naturally occurring alternative splicing variants of human CAR have been identified 133; 134; 135 . Functional characterization of these spliced CAR transcripts revealed that some are associated with altered expression, cellular localization, and chemical response of the receptor 136; 137; 138; 139 .…”
Section: Xenobiotic Receptor and Oxazaphosphorine Metabolismmentioning
confidence: 99%
“…One important feature of NR1I2 and NR1I3 is that ligandmediated receptor activation is species dependent, due to differences in the amino acid sequence of the ligand-binding domain (Gray, Peacock, & Squires, 2009;Gray, Pollock, Schook, & Squires, 2010). This issue makes comparisons of NR1I2 and NR1I3 activation between species difficult, although a limited number of selective ligands for rodent and hNR1I2 and hNR1I3 are available (Table 1) (Chan et al, 2011;Lemmen, Tozakidis, Bele, & Galla, 2013;.…”
mentioning
confidence: 99%
“…CAR is also absent in most fish species [76]. Compared to the more than 20 functional hCAR splice variants identified, far fewer CAR variants have been detected in other species, and only approximately five in the rat [77] and pig [78], most of which generate truncated protein products. Comparative genomic analyses show that mice, rats, and marmosets do not have a conserved CAR2 site and are thus incapable of generating a protein analogous to hCAR2.…”
Section: Carmentioning
confidence: 99%
“…This means that rodent models of DEHP toxicity will not accurately profile potential human toxicity because of their inability to generate a CAR2-like transcript. Porcine CAR (pgCAR) might be more homologous to human CAR than is rodent CAR, as is evidenced by the responses of pgCAR and hCAR to ligands being more similar than are those of hCAR and mCAR [78]. …”
Section: Carmentioning
confidence: 99%